IT financial management with Technology Business Management taxonomy: Implications for data-driven decision making - Rantanen, Vera (My University, 2024)
IT spending is increasing rapidly, and organizations need defined governance processes to manage and optimize IT spending. IT financial management (ITFM) is a governing function of IT focusing on the IT financials. Ensuring that an organization is using the right IT solutions by evaluating costs, benefits, and value of IT is not however a simple task. First, measuring IT business value is proved in many organizations to be a rather difficult activity. Second, there are many traditional challenges in IT financial management. For example, traditionally visibility to IT costs especially in different granularity levels has been inadequate and there has not been a common language with business to communicate the IT costs they are accountable for. The research focuses on Technology Business Management (TBM) taxonomy. TBM taxonomy has gained popularity among practitioners in large organizations in the recent years. It is said that TBM taxonomy connects all the needed components together to manage IT costs successfully. It is also said to be capable of solving some traditional challenges there are in the field. The aim of this thesis is to combine TBM taxonomy and data-driven decision making and study, how the implementation of TBM taxonomy (and the implementation of an ITFM system) can support data-driven decision making in IT financial management. Essentially, IT financial management is about decision making and making decisions based on data has become more important in the recent years. The research was conducted as a qualitative case study research. The data was collected in nine semi-structured interviews in the case organization. The data analysis was done using Gioia method. As a result, three data structures were created based on the data analysis. First, the areas where TBM taxonomy and the ITFM system can support data-driven decision making were identified to be Capabilities of doing ITFM, Optimizing IT spending and Transparency. Second, the areas where there were challenges a year after the implementation were Data, the Existing IT environment, the ITFM system characteristics and Using taxonomy to decision making. Finally, some of the areas where TBM taxonomy and the ITFM system were not able to support decision making at least during the interviews were for example benchmarking, internal work follow-up and value creation. The data structures also demonstrate the 1st and 2nd order codes in addition to the aggregate dimensions discussed. The research succeeded in its aim, but the research also faces some limitations. Due to limitations, the results may not be generalized to all organizations. Furthermore, there is not a lot of if any prior research available from TBM taxonomy. Therefore, the findings of this research could not have been evaluated towards prior research of TBM taxonomy but to the general prior research of IT financial management. Further research is needed to be conducted to generalize at least part of the results of this research and to increase the general understanding of using TBM taxonomy in IT financial management.

IT-menot kasvavat nopeasti, ja organisaatiot tarvitsevat määriteltyjä hallintoprosesseja IT-menojen hallintaan ja optimointiin. IT-taloushallinta on IT:n hallintotoiminto, joka keskittyy IT:n talouteen. Sen varmistaminen, että organisaatio käyttää oikeita IT-ratkaisuja arvioimalla IT:n kustannuksia, hyötyjä ja tuotettua arvoa, ei kuitenkaan ole yksinkertainen tehtävä. Ensinnäkin IT:n liiketoiminta-arvon mittaaminen on osoittautunut monissa organisaatioissa melko vaikeaksi aktiviteetiksi. Toiseksi IT-taloushallintaan liittyy monia perinteisiä haasteita. Esimerkiksi perinteisesti IT-kustannusten näkyvyys erityisesti eri tasoilla on ollut riittämätöntä, eikä liiketoimintayksiköiden kanssa ole ollut yhteistä kieltä, jolla olisi voitu kommunikoida IT-kustannuksista, joista he ovat vastuussa. Tässä tutkimuksessa keskitytään Technology Business Management (TBM) taksonomiaan. TBM taksonomia on viime vuosina saavuttanut suosiota suurten organisaatioiden käytännön toimijoiden keskuudessa. Sanotaan, että TBM taksonomia yhdistää kaikki tarvittavat osatekijät yhteen, jotta IT kustannuksia voidaan hallita onnistuneesti. Sen sanotaan myös kykenevän ratkaisemaan joitakin alalla esiintyviä perinteisiä haasteita. Tämän tutkielman tavoitteena on yhdistää TBM taksonomia ja datalähtöinen päätöksenteko ja tutkia, miten TBM taksonomian (ja IT-taloushallintajärjestelmän) käyttöönotto voi tukea datalähtöistä päätöksentekoa IT-taloushallinnassa. IT-taloushallinnassa on pohjimmiltaan kyse päätöksenteosta, ja datalähtöisten päätösten tekeminen on viime vuosina tullut entistä tärkeämmäksi. Tutkimus toteutettiin laadullisena tapaustutkimuksena. Aineisto kerättiin yhdeksässä puolistrukturoidussa haastattelussa case-organisaatiossa. Aineiston analyysi tehtiin Gioia-menetelmää käyttäen. Tuloksena luotiin kolme tietorakennetta aineiston analyysin perusteella. Ensinnäkin todettiin, että alueet, joissa TBM taksonomia ja IT-taloushallintajärjestelmä voivat tukea datalähtöistä päätöksentekoa, ovat Kyvykkyydet tehdä IT-taloushallintaa, IT-menojen optimointi ja Läpinäkyvyys. Toiseksi alueet, joissa oli haasteita vuoden kuluttua käyttöönotosta, olivat Data, Nykyinen IT ympäristö, IT-taloushallintajärjestelmän ominaisuudet ja Taksonomian käyttö päätöksenteossa. Lisäksi osa alueista, joilla TBM-taksonomia ja ITFM-järjestelmä eivät ainakaan haastattelujen aikana kyenneet tukemaan päätöksentekoa, olivat esimerkiksi benchmarking, sisäisen työn seuranta ja arvon luominen. Tietorakenteet sisältävät myös 1. ja 2. asteen koodit käsiteltyjen aggregaattiulottuvuuksien lisäksi. Tutkimus onnistui tavoitteessaan, mutta tutkimus kohtaa myös joitakin rajoituksia. Rajoitusten vuoksi tuloksia ei voida yleistää koskemaan kaikkia organisaatioita. Lisäksi TBM taksonomiasta ei ole saatavilla paljon, jos lainkaan, aiempaa tutkimusta. Tämän vuoksi tämän tutkimuksen tuloksia ei voitu arvioida TBM taksonomian aikaisempaan tutkimukseen nähden vaan IT-taloushallinnan yleiseen aiempaan tutkimukseen nähden. Lisätutkimusta tarvitaan, jotta voidaan yleistää ainakin osa tämän tutkimuksen tuloksista ja lisätä yleistä ymmärrystä TBM taksonomian käytöstä IT-taloushallinnassa.
Keywords: IT financial management, TBM taxonomy, data-driven decision making, IT-taloushallinta, TBM taksonomia, datalähtöinen päätöksenteko